Development of Nusa Ra Island as a Marine Tourism Object in Increasing Regional Original Income (PAD) in South Halmahera Regency - Hani Rusmin, Ummu; Awaluddin, Awaluddin; Ajadi, Memunat Tunarayo (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2024)
Purpose of the study: The purpose of this study is to understand, investigate, identify, and explain the formulation of research questions. This study aims to explain the development of tourism real estate carried out by the Tourism Office to increase local revenue in South Haramahera Regency. Methodology: This qualitative descriptive study uses inductive analysis to understand tourism management in the Banda Naira Islands. Data were collected through observation, purposive sampling interviews, and documentation, and analyzed using the Miles & Huberman model (reduction, presentation, conclusion drawing). The focus of the study includes constraints, strategies, and potentials of tourism management, with optimization of SO (Strengths-Opportunities) strategies to maximize local potential. Main Findings: Research shows that tourism development in the Banda Naira Islands is not optimal, especially in terms of tourist attractions, accessibility, facilities, and management. The potential for marine and historical tourism is great, but the lack of artificial attractions, transportation facilities, and facilities such as information centers, public toilets, and waste management are obstacles. Destination management is also not structured. An SO (Strengths-Opportunities) strategy is recommended with institutional strengthening, infrastructure improvement, and stakeholder collaboration to optimize local potential and tourist attractions. Novelty/Originality of this study: This research presents novelty in the development of Nusa Ra Island as a marine tourism with a sustainable approach that integrates nature conservation, local community empowerment, and promotion through digital technology.